a)f(x)=(8x^5-5x^8)^12

б)f(X)=(1/9 - 3x³)^27

в) f(x)=(4x^10-5x)^10

г)f(x)=(x^5-4x^4)^130

Вычислите производные функций

ответы

б)-81x² (1/9-3x³)^26

г)130x³(5x-16)(x^5-4x^4)^129

2

Ответы и объяснения

  • Yena
  • главный мозг
2013-02-28T13:14:08+04:00

a)f(x)=(8x⁵-5x⁸)¹²

  f ' (x)=12(8x⁵-5x⁸)¹¹ * (40x⁴-40x⁷)

 

б) f(X)=(1/9 - 3x³)²⁷  ваш ответ не верный

      f ' (x)=27(1/9-3x³)²⁶ * (-9x²)=-243x²(1/9-3x³)²⁶

 

в) f(x)=(4x^10-5x)^10

     f ' (x)=10(4x¹⁰-5x)9 *(40x⁹-5)

  

г) f(x)=(x^5-4x^4)^130

    f ' (x)=130(x⁵-4x⁴)¹²⁹ * (5x⁴-16x³)

 

Лучший Ответ!
  • Katyuha85
  • почетный грамотей
2013-02-28T13:19:47+04:00

a)f(x)=(8x⁵-5x⁸)¹²

f ' (x) = ((8x⁵-5x⁸)¹²) ' = 12*(8x⁵-5x⁸)¹¹ * (8x⁵-5x⁸) ' = 12*(8x⁵-5x⁸)¹¹ * (40x⁴-40x⁷) = 12*(8x⁵-5x⁸)¹¹ * 40x⁴(1-x³) = 480x⁴ * (8x⁵-5x⁸)¹¹ * (1-x³)

 

б)f(X)=(1/9 - 3x³)²⁷

f ' (x) = ((1/9 - 3x³)²⁷) ' = 27(1/9 - 3x³)²⁶ * (1/9 - 3x³) ' =  27(1/9 - 3x³)²⁶ * (-3*3x²) = 27(1/9 - 3x³)²⁶ * (-9x²) = -243x² * (1/9 - 3x³)²⁶

 

в) f(x)=(4x¹⁰-5x)¹⁰

f ' (x) = ((4x¹⁰-5x)¹⁰) ' = 10(4x¹⁰-5x)⁹ * (4x¹⁰-5x) ' =  10(4x¹⁰-5x)⁹ * (40x⁹-5)= 10(4x¹⁰-5x)⁹ * 5(8x⁹-1)=50(4x¹⁰-5x)⁹ * (8x⁹-1)

 

г)f(x)=(x⁵-4x⁴)¹³⁰

f ' (x) = ((x⁵-4x⁴)¹³⁰) ' = 130(x⁵-4x⁴)¹²⁹ * (x⁵-4x⁴) ' = 130(x⁵-4x⁴)¹²⁹ * (5x⁴-16x³) = 130(x⁵-4x⁴)¹²⁹ * x³(5x-16) = 130*x³ * (x⁵-4x⁴)¹²⁹ * (5x-16)